Implementasi Load Balancing Internet Guna Peningkatan Akses Pengguna Pada Kantor Dinas BPKAD Kabupaten Sorong Selatan - Indriyanta, Gani; Haryono, Nugroho Agus; Waluyo, Prihadi Beny (Patria : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract — The network infrastructure at BPKAD (( Badan Pengelolaan Keuangan dan Aset Daerah) of South Sorong Regency has been established to provide connection access for each section head and relevant staff to the SIMDA server. To cater to internet needs, the BPKAD Office has subscribed to four distinct internet lines. This separate network topology poses challenges and limitations, such as immobility, instability, and suboptimal quota settings. To address this, the UKDW Team restructured the network topology at BPKAD. Community service is implemented using a Community-Based Research approach, where partners play an active role and collaborate in various aspects, from modeling the network needs analysis, establishing an integrated and seamless network, to preparing human resources. The network was redesigned by integrating the four internet lines, facilitating uninterrupted network connections, bandwidth management, user management, and load balancing settings. Activities were evaluated through successful connection tests, and access restrictions have been set for each user. The community service activity has been successfully conducted, evidenced by the increased satisfaction of office staff in accessing the internet. Internet usage has become more secure, and partners are now capable of resolving their issues independently.